Penguatan Nilai Bela Negara Di SMA Negeri Kalisat: Proyek Garda Nusa - Asathinuz Zaman Aryakhiya; Dimas Zaqy Firdausi; Hany Shofia Naela; Muhamad Wahid Agus Prasetyo; Nazwa Ramadhani; Tantut Susanto (Universitas Muhammadiyah Gresik, 2025)
Socialization of national defense is an important step to instill national values and patriotism among the younger generation. In order to introduce the importance of defending the state, Kalisat Public High School held the Garda Nusa project on November 23, 2024, aimed at increasing students' awareness of their role in maintaining and defending the Unitary State of the Republic of Indonesia (NKRI). This project is designed to provide a deeper understanding of national values, as well as to encourage students to actively participate in activities that support the progress of the nation. The method used was a questionnaire distributed before and after the socialization to measure changes in students' understanding and attitudes towards national defense. The research results show a significant increase in students' knowledge and attitudes towards the importance of defending the country. Most students showed readiness to participate in activities that support the integrity of the Unitary State of the Republic of Indonesia (NKRI), both in daily life and in social service. This Garda Nusa project proves that socializing love for the country at the secondary education level can effectively shape the national character of students.